The effect of negative pressure wound therapy on necrotizing fasciitis following total abdominal hysterectomy: a case report - Zahra Yazdi; Monireh Mirzaie; Marzieh Savari; Narges Farshadpour; Morteza Sedaqat (Journal of the Egyptian Women’s Dermatologic Society)
Negative pressure wound therapy or Vacuum therapy of a wound is a sort of therapy to aid wounds to heal by decreasing air pressure on the wound. A 69-year-old female was admitted due to large leiomyoma who underwent a total abdominal hysterectomy. During hospitalization, the incision site of the patient changed color and the patient had a mild fever with an initial diagnosis of necrotizing fasciitis. The patient had debridement four times and no remarkable improvement was achieved due to the extent and depth of the wound. Therefore, vacuum therapy was performed for the patient and after applying this procedure, the patient’s wound got smaller and healed with frequent follow–up and the administration of appropriate antibiotics. Wound care is one of the important steps after that total abdominal hysterectomy and vacuum therapy is useful and safe method for faster healing with satisfactory results for its wounds.